Periprocedural changes in natriuretic peptide levels and clinical outcome after transcatheter mitral valve repair. (14th September 2021) - Tanaka, Tetsu; Kavsur, Refik; Spieker, Maximilian; Iliadis, Christos; Metze, Clemens; Horn, Patrick; Sugiura, Atsushi; Kelm, Malte; Baldus, Stephan; Nickenig, Georg; Westenfeld, Ralf; Pfister, Roman; et al.
Abstract: Aims: This multicentre study investigated the association of periprocedural changes in the levels of N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) with clinical outcomes after transcatheter edge‐to‐edge mitral valve repair (TMVR). Methods and results: Patients were retrospectively analysed who underwent TMVR with the MitraClip system (Abbott Vascular, Santa Clara, CA, USA) and had available sequential NT‐proBNP testing at baseline and 2 months after TMVR. Periprocedural changes in NT‐proBNP following TMVR were assessed as the percent change in NT‐proBNP between baseline and the 2 month follow‐up, and the significant reduction in NT‐proBNP was defined as a decrease of >30% in the follow‐up NT‐proBNP compared with the pre‐procedural NT‐proBNP level. Primary outcome was defined as a composite outcome consisting of all‐cause mortality and hospitalization due to heart failure from 2 months to 2 years after TMVR. Additionally, we identified the cut‐off value of pre‐procedural NT‐proBNP to predict the composite outcome using a receiver operating characteristic analysis (cut‐off: 2485 pg/mL). Of 485 patients undergoing TMVR (age: 76.2 ± 9.2 years, female: 42.1%, secondary mitral regurgitation: 67.2%), 150 patients (30.9%) had the significant reduction in NT‐proBNP (>30%) following the procedure. Patients with the NT‐proBNP reduction had a lower incidence of the composite outcome, compared with those without the reduction in NT‐proBNP (31.4% vs. 40.2%; log‐rank P = 0.03). The significant reduction in NT‐proBNP was also associated with a lower risk of the composite outcome [adjusted hazard ratio (HR): 0.67; 95% confidence interval (CI): 0.45–0.97; P = 0.04], independently of pre‐procedural NT‐proBNP levels and other clinical parameters. The percent change in NT‐proBNP was associated with a linear trend of the incidence of the composite outcome (adjusted HR per 10% decrease: 0.96; 95% CI: 0.94–0.98; P < 0.001). A stratified analysis revealed that the prognostic impact of the significant reduction in NT‐proBNP was consistent among clinical subgroups, including aetiology of mitral regurgitation ( P for interaction = 0.99). Higher pre‐procedural NT‐proBNP level (>2485 pg/mL) was associated with the increased risk of the composite outcome (adjusted HR: 1.50; 95% CI: 1.03–2.17; P = 0.03); however, patients with a higher pre‐procedural NT‐proBNP who achieved the significant reduction in NT‐proBNP had a similar risk of the composite outcome to those with a lower pre‐procedural NT‐proBNP. Conclusions: Changes in sequential NT‐proBNP measurements were associated with clinical outcomes within 2 years after TMVR. The assessment of NT‐proBNP dynamics may be valuable to assess the residual risk for patients undergoing TMVR and could assist with post‐procedural management after TMVR.